The Influence of Interactive Learning Media for Writing Poetry Based on the Kompasiana Platform on the Merdeka Curriculum for Class XI of SMA Negeri 1 Bulakamba - Sufrayit, Alif; Nisa, Hany Uswatun; Kurniawan, Praseyto Yuli (Peneliti.net, 2024)
The aims of this research are: (1) to describe learning to write poetry without using interactive learning media based on the Kompasiana platform, (2) to describe learning to write poetry using interactive learning media based on the Kompasiana platform, and (3) to test the effect of interactive learning media based on the Kompasiana platform in writing poetry in the Independent Curriculum Class XI SMA Negeri 1 Bulakamba. This research uses a quantitative approach with quasi-experimental methods, especially the Nonequivalent Control Group Design. Data was collected using test and non-test instruments. The research results showed that: (1) in the control class, the lowest pretest score was 55 and the highest was 80 with an average of 66.00. The lowest posttest score was 65 and the highest was 85 with an average of 71.60; (2) in the experimental class, the lowest pretest score was 55 and the highest was 75 with an average of 66.80. The lowest posttest score was 70 and the highest was 95 with an average of 80.80; (3) The influence test shows that interactive learning media based on the Kompasiana platform significantly influences the ability to write poetry in the Merdeka Curriculum in class XI of SMA Negeri 1 Bulakamba. The t test results show a significant difference between the posttest results of the control and experimental classes with a calculated t value of 5.365 and a t table of 1.714, which shows t calculated > t table at the 95% confidence level. Therefore, interactive learning media based on the Kompasiana platform is effective in improving the ability to write poetry in the Merdeka Curriculum in class XI of SMA Negeri 1 Bulakamba.